Drying model for small tumbled beef pieces (biltong) at ambient and mild air temperatures. (20th October 2021) - Arnaud, Elodie; Collignan, Antoine; Courtois, Francis
Abstract: The literature on the modeling of meat drying mainly focuses on large pieces of pork with very few studies on small pieces of beef, particularly when previously tumbled with salt and vinegar. In this study, the drying kinetics of tumbled small pieces of beef (biltong) were investigated experimentally using a pilot dryer that allowed precise control of the air conditions. The kinetics were then modeled using a two‐compartment model that mimicked the diffusion model. Results showed that two experimental drying kinetics were enough to identify model parameters and to mimic the drying behavior of biltong of different sizes subjected to a wide range of drying conditions (25–55°C, 30–40% relative humidity). The model also produced acceptable results (mean error on moisture content < 0.1 d . b . and r 2 > .99 ) for simulating biltong drying in industrial conditions. This model can be used as a sizing tool for small and medium drying plants in southern Africa. Practical Applications: Drying is widely used to process traditional meat products such as the salted/dried biltong in South Africa. The final product and the manufacturing process used to produce biltong are well described by Jones in 2017. Biltong is original because it is made of strips of meat while up to now, modeling studies have mainly dealt with large meat muscles, like dried cured ham. Biltong, on the other hand, resembles to many other salted/dried products made from small meat muscles all over the world or meat strips mainly in developing countries but not only, for example jerky in the United States. The model developed will be useful for the prediction of drying time by processors who wants to ensure their end product remain stable and have to cope with variations in the size of the meat strips and in the temperature of the drying air. Abstract : Results showed that two experimental drying kinetics were enough to identify model parameters and to mimic the drying behavior of biltong of different sizes subjected to a wide range of drying conditions (25–55°C, 30–40% relative humidity). The model also produced acceptable results (mean error on moisture content < 0.1 d.b. and r²>.99 ) for simulating biltong drying in industrial conditions.